Algorithms Used in Detection of Cardiovascular Diseases - Magrupov, T. M.; Isroiljon kizi, Akbarova Anora (American Journal of Bioscience and Clinical Integrity, 2026)
The article analyzes modern algorithms and methods used in the early detection of cardiovascular diseases (CVD). The study examined the effectiveness of classification algorithms based on machine learning and artificial intelligence. The results obtained will serve to increase the accuracy of medical diagnostic systems.